Antimicrobial Properties of Actively Purified Secondary Metabolites Isolated from Different Marine Organisms - Bamunuarachchi, Nilushi I.; Khan, Fazlurrahman; Kim, Young-Mog (Current Pharmaceutical Biotechnology, 2021)
Background: The treatment of infection caused by pathogenic bacteria becomes one of the serious concerns globally. The failure in the treatment was found due to the exhibition of multiple resistance mechanisms against the antimicrobial agents. The emergence of resistant bacterial species has also been observed due to prolong treatment using conventional antibiotics. To combat these problems, several alternative strategies have been employed using biological and chemically synthesized compounds as antibacterial agents. Marine organisms are considered as one of the potential sources for the isolation of bioactive compounds due to the easily available, cost-effective, and eco-friendly. Methods: The online search methodology was adapted for the collection of information related to the antimicrobial properties of marine-derived compounds. These compound has been isolated and purified by different purification techniques, and their structure also characterized. Furthermore, the antibacterial activities have been reported by using broth microdilution as well as disc diffusion assays. Results: The present review paper describes the antimicrobial effect of diverse secondary metabolites which are isolated and purified from the different marine organisms. The structural elucidation of each secondary metabolite has also been done in the present paper, which will help for the in silico designing of the novel and potent antimicrobial compounds. Conclusion: A thorough literature search has been made and summarizes the list of antimicrobial compounds that are isolated from both prokaryotic and eukaryotic marine organisms. The information obtained from the present paper will be helpful for the application of marine compounds as antimicrobial agents against different antibiotic-resistant human pathogenic bacteria.
Keywords: secondary metabolites